2020
DOI: 10.1111/jce.14761
|View full text |Cite
|
Sign up to set email alerts
|

A new clinical risk score for predicting the prevalence of low‐voltage areas in patients undergoing atrial fibrillation ablation

Abstract: Introduction: Although the presence of left atrial low-voltage areas (LVAs) is strongly associated with the recurrence of atrial fibrillation (AF) after ablation, few methods are available to classify the prevalence of LVAs. The purpose of this study was to establish a risk score for predicting the prevalence of LVAs in patients undergoing ablation for AF. Methods: We enrolled 1004 consecutive patients who underwent initial ablation for AF (age, 68 ± 10 years old; female, 346 (34%); persistent AF, 513 (51%)). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The higher prevalence of LVAs in women, which has been previously reported, 12,13 was confirmed across broad age and left atrial size groups. Several sex-specific pathophysiological features can be noted.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The higher prevalence of LVAs in women, which has been previously reported, 12,13 was confirmed across broad age and left atrial size groups. Several sex-specific pathophysiological features can be noted.…”
Section: Discussionsupporting
confidence: 82%
“…Women also had higher clinical scores predicting the presence of LVAs (SPEED and DR-FLASH). 11,12 On echocardiography, women patients had smaller atrial and ventricular chamber sizes, a higher left ventricular ejection fraction, and lower left ventricular mass.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study reported that the presence of LVZ can be predicted by pre-procedural markers (sex, age, diabetes, type of AF, brain natriuretic peptide). 28) Whether delayed gadolinium enhancement in cardiac magnetic resonance imaging correlates with LVZ acquired with electroanatomic mapping is another interesting area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] The ANP/BNP ratio was also compared based on the DR-FLASH score and SPEED score, which represent risk scores for predicting LVAs. 30,31 Kaplan-Meier analysis and the log-rank test were used to investigate the association between the longterm outcomes and the ANP/BNP ratio. In Kaplan-Meier analysis and the log-rank test, cut-off of the ANP/BNP ratio was set to the median value of 0.65.…”
Section: Methodsmentioning
confidence: 99%